2020
DOI: 10.1002/anie.201915766
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Conversion of Waste Plastics into C2 Fuels under Simulated Natural Environment Conditions

Abstract: Reported here is the first highly selective conversion of various waste plastics into C2 fuels under simulated natural environment conditions by a sequential photoinduced C−C cleavage and coupling pathway, where single‐use bags, disposable food containers, food wrap films, and their main components of polyethylene, polypropylene, and polyvinyl chloride can be photocatalytically transformed into CH3COOH without using sacrificial agents. As an example, polyethylene is photodegraded 100 % into CO2 within 40 h by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
216
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(216 citation statements)
references
References 28 publications
0
216
0
Order By: Relevance
“…Solar‐driven biomass upgrading and their reforming to H 2 offer a straightforward and low‐energy way to convert wastes into renewable fuels, which efficiently utilize the photo‐generated holes and simultaneously boost photocatalytic H 2 production. [ 19,20 ] For instance, Reisner and co‐workers reported the photoreforming of cellulose, lignin, and hemicellulose to H 2 using semiconducting CdS quantum dots as photocatalysts in alkaline aqueous solution. During the photoreforming process, the photocatalyst provided electrons for the reduction of protons to produce H 2 through biomass oxidation, and achieved the high activity of H 2 generation without CdS photocorrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Solar‐driven biomass upgrading and their reforming to H 2 offer a straightforward and low‐energy way to convert wastes into renewable fuels, which efficiently utilize the photo‐generated holes and simultaneously boost photocatalytic H 2 production. [ 19,20 ] For instance, Reisner and co‐workers reported the photoreforming of cellulose, lignin, and hemicellulose to H 2 using semiconducting CdS quantum dots as photocatalysts in alkaline aqueous solution. During the photoreforming process, the photocatalyst provided electrons for the reduction of protons to produce H 2 through biomass oxidation, and achieved the high activity of H 2 generation without CdS photocorrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in the recycle degradation of P2, the activity of TiO 2 @GO remained about 88% after three times recycle degradations in Figure 6, revealing its high photocatalytic stability. In this study, it was strongly demonstrated the polymers underwent a photoox tive C-C bond cleavage process to get the CO2, H2O, and ROX with TiO2@GO as photocatalyst in a natural environment [23][24][25]. The photocatalytic propertie TiO2@GO were well-researched, as shown in Scheme 3 [26].…”
Section: Resultsmentioning
confidence: 87%
“…The accumulated h were oxidative reaction with the H2O to produce •OH, and simultaneously the elec and H + was also interacted with the O2 to bring the H2O2, leading to achieving the radation of polymers. In this study, it was strongly demonstrated the polymers underwent a photooxidative C-C bond cleavage process to get the CO 2 , H 2 O, and RO X with TiO 2 @GO as the photocatalyst in a natural environment [23][24][25]. The photocatalytic properties of TiO 2 @GO were well-researched, as shown in Scheme 3 [26].…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Besides one-step conversion, Xie, and co-workers (Jiao et al, 2020) recently have reported a sequential photoinduced C-C cleavage under atmosphere and C-C bond coupling in the absence of oxygen, which for the first time realizes highly selective conversion of various waste plastic into C 2 fuels under simulated natural environment (room temperature, pure water, and simulated one-sun irradiation; Supplementary Figure 6A). In the research, single-unit-cell thick Nb 2 O 5 layers (2.96 nm) is prepared from niobic acid atomic layer precursor as catalyst (Supplementary Figure 6B), due to its high redox potentials, valence band maximum at + 2.5 V vs. NHE and the conduction band minimum at 0.9 V vs. NHE at pH 7, which is conducive for maximal exposure of active site and thus promoting the light conversion performance.…”
Section: Photocatalytic Plastic Degradation Coupled With Sequential Co 2 Reduction To Produce C 2 Fuelsmentioning
confidence: 99%